Physical activity of students before and during COVID-19 lockdown in Spain - Vegara Ferri, José Miguel; Angosto, Salvador; Carboneros, María; López Gullón, José María; Gámez Payá, Javier (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The closure of educational centers was one of the first measures against COVID-19, preventing physical education in classrooms. The aim of this study is to analyze the physical activity practice of adolescent students before and during the COVID-19 lockdown period in Spain. A total of 4508 high school students with a mean age of 15.8 years (±1.1 years) completed the IPAQ Questionnaire short version. The results show how students significantly decreased the duration and frequency of physical activity during confinement. The expenditure in MET-minutes/week has decreased by 46.8%, highlighting the low intensity activity "walking" which has decreased by 91.1% between both periods. The percentage of students performing a low level of physical activity has increased from 24.1% before confinement to 41.3% during this period. However, 36% of the students performing a low level of physical activity before quarantine have gone on to perform a medium or high level of physical activity during quarantine. These results help to understand and analyze the behavior of adolescent students during the lockdown period.